State of knowledge on the occupational exposure to carbon nanotubes - Guseva Canu, I.; Batsungnoen, K.; Maynard, A.; Hopf, N.B. (International journal of hygiene and environmental health, 2020)
Carbon nanotubes (CNT) trigger fascination as well as anxiety, given their unique physical and chemical properties, and continuing concerns around their possible health effects. CNT exposure assessment is an integral component of occupational and environmental epidemiology, risk assessment, and management. We conducted a systematic review to analyze the quality of CNT occupational exposure assessments in field studies and to assess the relevance of available quantitative data from occupational hygiene and epidemiological perspectives. PubMed and Scopus databases were searched for the period 2000–2018. To grade the quality of each study, we used a standardized grid of seven criteria. The first criterion addressed 12 items deemed most relevant CNT physical-chemical properties with respect to their in vitro and in vivo toxicity. We included 27 studies from 11 countries in the review and graded them high (n = 2), moderate (n = 15) and low quality (n = 10). Half of the studies measured elemental carbon mass concentration (EC) using different methods and aerosol fractions. In 85% of studies, the observed values exceed the US National Institute for Occupational Safety and Health Recommended Exposure Limit. The quantification of CNT agglomerates and/or CNT contained fibers becomes increasingly common although lacking methodological standardization. Work activities with the greatest mean CNT mass concentrations were non-enclosed and included sieving, harvesting, packaging, reactor cleaning, extrusion and pelletizing. Some of the large studies defined standardized job titles according to exposure estimates at corresponding workstations and classified them by decreasing CNT exposure level: technicians > engineers > chemists. The already initiated harmonization of CNT exposure assessment and result reporting need to continue to favor not only studies in the field, but also to identify companies and workers using CNTs to characterize their exposures as well as monitor their health. This will enable an objective and realistic evaluation of risks associated with CNT applications and an appropriate risk management.